Effect of pre-harvest calcium silicate on post-harvest quality of tomatoes (Research, Society and Development, 2020)
The present work evaluated the influence of calcium silicate on the polygalacturonase enzyme activity, respiration, ethylene, and the physicochemical characteristics on the post-harvest quality of two tomato hybrids. The experimental design was of randomized blocks, with four repetitions in protected cultivation environment. The treatments were distributed in a 2 x 5 factorial scheme, corresponding to the hybrids (Ivety and Natalia) and five doses of calcium silicate (0, 150, 300, 450 and 600 kg ha-1), which were applied on the same day as the pots were filled. Evaluations were carried out on the fruits, namely: ethylene production, fruit respiration, firmness, number of loculus, polygalacturonase activity, total carotenoids, lycopene, phenolic compounds, soluble solids content, pH, titratable acidity and ascorbic acid content.  The application of calcium silicate provided the reduction of ethylene production and fruit respiration. Natalia hybrid showed low polygalacturonase activity, this difference being due to genetic variabilityThe increase of calcium silicate doses provided the reduction of polygalacturonase enzyme concentration due to its constitution in the cell wall. The concentrations of lycopene, phenolic compounds, soluble solids, pH, titratable acidity and ascorbic acid in the fruits increased in response to the increasing doses of calcium silicate for 'Ivety'. Hybrids present distinct behaviors on the influence of the fertilization of tomatoes with calcium silicate, which can increase the post-harvest conservation and improve the physical-chemical characteristics of tomato fruits.